A comprehensive review for artificial intelligence on neuroimaging in rehabilitation of ischemic stroke - Zhao, Zijian; Zhang, Yuanyuan; Su, Jiuhui; Yang, Lianbo; Pang, Luhang; Gao, Yingshan; Wang, Hongbo (Frontiers in Neurology, 2024)
Stroke is the second leading cause of death worldwide, with ischemic stroke accounting for a significant proportion of morbidity and mortality among stroke patients. Ischemic stroke often causes disability and cognitive impairment in patients, which seriously affects the quality of life of patients. Therefore, how to predict the recovery of patients can provide support for clinical intervention in advance and improve the enthusiasm of patients for rehabilitation treatment. With the popularization of imaging technology, the diagnosis and treatment of ischemic stroke patients are often accompanied by a large number of imaging data. Through machine learning and Deep Learning, information from imaging data can be used more effectively. In this review, we discuss recent advances in neuroimaging, machine learning, and Deep Learning in the rehabilitation of ischemic stroke.